Use of CPWL approximations in the design of a numerical nonlinear regulator - Padín, Mirta S. (2000)
This paper presents the state regulation problem for nonlinear plants with initial conditions in a given bounded region, proposed originally by Kreisselmeier and Birkholzer (1994). An efficient computer implementable algorithm is presented, based on canonical piecewise linear approximation for the discrete model of the plant.